Green Accounting Fails to Enhance Financial Performance in Indonesia: Akuntansi Hijau Gagal Meningkatkan Kinerja Keuangan di Indonesia - Indiani, Ayunia Suci; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of green accounting and company characteristics on financial performance through environmental disclosure for manufacturing and consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2017-2020. Using a sample of 17 companies selected via purposive sampling, secondary data were analyzed with Partial Least Square (PLS). The results indicate that green accounting and company characteristics positively influence environmental disclosure, but do not affect financial performance through it. Additionally, environmental disclosure does not impact financial performance. These findings suggest that while environmental reporting is enhanced by green accounting and company traits, it does not directly improve financial outcomes. Highlight: Green accounting and company traits boost environmental disclosure. Environmental disclosure doesn’t affect financial performance. Focus: manufacturing and consumer goods firms on IDX (2017-2020). Keywords: Green Accounting, Environmental Disclosure, Financial Performance, Company Characteristics, IDX